PERAN POLA ASUH DALAM PENCEGAHAN STUNTING PADA ANAK BALITA USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS TANJUNG - Mursyida, Rikhly Faradisy; Dian Ika Puspitasari; Eko Mulyadi (Jurnal Medicare, 2025)
Stunting is a failure to thrive in children caused by a lack of nutritional intake for a long time, this is one of the nutritional problems that is a major concern in Indonesia, namely 19.8% still has not reached the national target set at 14% by the end of 2024. The purpose of this study: to analyze the relationship between the role of parenting patterns in preventing stunting in toddlers aged 24-59 months in the Tanjung Health Center Work Area. This study was designed quantitatively with a cross-sectional approach. The population was mothers who had children aged 24-59 months. The sample was 63 people using a simple random sampling method. The independent variable is parenting patterns, the dependent variable is the incidence of Stunting. Data collection using a questionnaire sheet. Statistical analysis with the Chi-Square test guided by the results of the Fisher's Exact Test, α <0.05. The results of the study showed that respondents with a democratic mother's parenting pattern were 52 respondents (82%), toddlers with normal height were 51 toddlers (98%) and the results of the Chi-Square statistical test were (ρ 0.003 <0.05). The conclusion of the study is that there is a relationship between parenting patterns and the incidence of Stunting in toddlers aged 24-59 months, in mothers of toddlers with appropriate parenting patterns in feeding, namely democratic parenting patterns, there is a tendency for toddlers not to experience Stunting.